2016
DOI: 10.1186/s12284-016-0136-z
|View full text |Cite
|
Sign up to set email alerts
|

SMALL GRAIN 11 Controls Grain Size, Grain Number and Grain Yield in Rice

Abstract: BackgroundGrain size is one of key agronomic traits that determine grain yield in rice. Several regulators of grain size have been identified in rice, but the mechanisms that determine grain size and yield remain largely unknown.ResultsHere we characterize a small grain (smg11) mutant in rice, which exhibits small grains, dense panicles and the increased number of grains per panicle. Cloning and sequence analyses of the SMG11 gene reveal that smg11 is a new allele of DWARF2 (D2), which encodes a cytochrome P45… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
85
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(86 citation statements)
references
References 41 publications
(74 reference statements)
1
85
0
Order By: Relevance
“…The genomic DNAs from Xiushui09 and Changlixian were also resequenced as control. The candidate causal genes were identified as described before (Fang et al, 2016). Six and three candidate causal SNPs for large8-1 and large8-2 were identified, respectively (Tables S1 and S2).…”
Section: Identification Of the Large8 Genementioning
confidence: 99%
See 1 more Smart Citation
“…The genomic DNAs from Xiushui09 and Changlixian were also resequenced as control. The candidate causal genes were identified as described before (Fang et al, 2016). Six and three candidate causal SNPs for large8-1 and large8-2 were identified, respectively (Tables S1 and S2).…”
Section: Identification Of the Large8 Genementioning
confidence: 99%
“…MutMap approach was used to identifying the candidate genes for the large8-1 and large8-2 mutants (Abe et al, 2012;Fang et al, 2016).…”
Section: Molecular Cloning Of Large8/osmkp1mentioning
confidence: 99%
“…Comparison of the grain size of ah2 mutant with its wild‐type showed that the grain length and width of the ah2 mutant were reduced by 15.2% and 8.4%, respectively, compared with the wild‐type. Several known genes that affect grain size by modulating cell proliferation and expansion have been reported, which include GL7/GW7, BG1 , GS2, GL3 , GS3, GS5, DSG1 , GW2 , and GW8 (Duan et al ., ; Fang et al ., ). The GL7/GW7, GS2, GL3 , DSG1 , GW2 , and GW8 transcript levels were higher in the ah2 mutant than in the wild‐type, consistent with the ah2 phenotype.…”
Section: Discussionmentioning
confidence: 97%
“…Grain size, which is an important agronomic trait in many crops, is determined by grain width, grain length and grain thickness [35]. Although some genes that manipulate seed size have been identified in crop plants [36], the molecular mechanisms that regulate seed size are still poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of full length amino acid sequence conserved domain and similarity, we subdivided the 171 typical members of the MADS gene family into 5 groups (designated MIKC, Mα, Mβ, Mγ, Mδ), according to the previous classification of MADS proteins from Arabidopsis [9]. Of the 63 inferred physic nut JcMADS proteins, thirty-two were assigned to group MIKC (JcMADS03, 04, 05, 07, 12,16,17,19,20,22,24,25,26,27,28,29,31,32,37,38,42,44,46,47,49,50,52,53,54,55,56,63), thirteen to group Mα (JcMADS01, 06, 08, 11,13,14,33,35,39,43,57,58,59), four to group Mβ (JcMADS09, 48, 51, 60), six to group Mγ (JcMADS10, 15,34,36,41,62) and eight to group Mδ (JcMADS02, 18,21,23,30,40,45,…”
Section: Phylogenetic Relationships Of the Jcmads Proteinsmentioning
confidence: 99%